Prevalência da infecção por HPV e perfil das mulheres frente ao exame de papanicolau no município de São José de Mipibú/RN. - Nascimento, Ermeton Duarte do (2008)
The Human Papillomavirus (HPV) infection is the major sexually transmitted disease all over the world. There are many factors associated to infection and the virus persistency in the organism. This study aims to evaluate the women's knowledge, attitudes and practice about the Papanicolaou test (Pap), as well as analyze the HPV and Chlamydia trachomatis infections prevalences in sexually active women from the city of São José do Mipibu/RN/Brazil. This research was divided in two steps (step I and step II), using different methodologies and samples each. The samples collected in each step, even socio-demographic or from uterus cervix, are from different patients e were analyzed separated. In step I was evaluated 267 rural and urban zone women s knowledge, attitudes and practices about the Pap by home interview. In the step II were included 605 women with age ranged from 15 to 71 years old, with mean of 33,5 years old and from each one were collected two cervical samples, one for Pap and other for molecular biology, beside the epidemiological interview to investigate the correlation between prevalence of HPV infection and risk factors. To molecular analyses, the samples were processed using a mammal rapid DNA extraction technique protocol. For C. trachomatis DNA detection were used the CP24/27 primers, and GP5+/GP6+ to HPV. PCR products were analyzed by electrophoresis on 8% polyacrylamide gels, followed by silver staining. The results of the step I showed that, in spite of only 46,1% of the interviewed women they have demonstrated to possess appropriate knowledge on the Pap test, the attitude and practice proportions were significantly larger, 63,3% and 64,4% respectively. The largest education degree presented association with adaptation of the knowledge, attitudes and practice, while neglect, lack of solicitation of the exam for the doctor and shame, came as main barriers for the accomplishment of the exam. In the stage II the HPV general prevalence was 28,9%, being 26,7% in the women with normal cytology or benign alterations, 26,7% in the ones that had atypical squamous cells of undetermined significance (ASC-US) and 80% in those with Low grade squamous intraepithelial lesion (LSIL). the HPV infection prevalence was larger in the patients with up to 30 years of age and in the unmarried women, and those that had more than one sexual partner presented larger infection risk. The results show that the sexual relationship with multiple partners increased the infection risk for HPV and consequently the possibility of the occurrence of lesions uterine cervix